Collective climate action: Determinants of participation intention in community-based pro-environmental initiatives - Bamberg, Sebastian; Rees, Jonas; Seebauer, Sebastian (Journal of environmental psychology, 2015)
There seems to be consensus that apart from individual behavioral change, system-wide transformations are required to address the challenges posed by climate change. Collective action is viewed as one core mechanism in social transformation but there is currently no systematic research on collective climate action. By reviewing theoretical perspectives and models explaining collective protest, we aim to provide a starting point for such a research program. Based on correlational data from a student sample (N = 652), a sample of participants of a local climate protection initiative (N = 71), and visitors of a climate protection event (N = 88), we tested constructs derived from these theoretical models. Social identity, perceived behavioral control, and participative efficacy beliefs consistently predicted substantial amounts of variance in participation intention. Implications for future research are discussed, such as recognizing the interplay between cost-benefit calculations and social identity, or temporal dynamics in collective action engagement. •Collective action has historically been a motor of social transformation.•A host of theories and models has been developed in the realm of collective protest.•We transfer and test these models in the context of collective climate action.•Social identity was the core predictor of collective climate action across studies.